1998
DOI: 10.1557/jmr.1998.0277
|View full text |Cite
|
Sign up to set email alerts
|

Downshift of Raman peak in diamond powders

Abstract: Results are presented on the influence of the size of diamond powders and the laser power on the main Raman line. These results show conclusively that there is a consistent and systematic, reversible, downshift with both decrease of powder size, and increase of power. The shift can be explained by local heating of about 500 °C in the extreme case. Its significance applies to interpretation of the alleged “downshifting” of the 1332 cm−1 line in all diamond research. In the future, the grain size, the thermal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…The first-order Raman band (F 2g ) of diamond occurs at wavenumber 1332 cm −1 and represents the main C-C bond vibration in diamond. A shift of this Raman peak to lower wavenumbers is a well-known effect occurring at very small crystallite sizes (Zhao et al 1998). It can also vary as a function of lattice stress, presence of lonsdaleite, or of temperature, which, in turn, depends on the incident laser power (Miyamoto 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The first-order Raman band (F 2g ) of diamond occurs at wavenumber 1332 cm −1 and represents the main C-C bond vibration in diamond. A shift of this Raman peak to lower wavenumbers is a well-known effect occurring at very small crystallite sizes (Zhao et al 1998). It can also vary as a function of lattice stress, presence of lonsdaleite, or of temperature, which, in turn, depends on the incident laser power (Miyamoto 1998).…”
Section: Resultsmentioning
confidence: 99%
“…34 Additionally, the peak shifts were observed due to the heating up of a measurement target by probing laser. 13,35,36 In our case, the typical sizes of the crystal grains are larger than 100 nm (see Fig. 2 (b)) which seems to be rather large to discuss the internal stress causing the observed relatively large peak shifts of around 10 cm -1 .…”
Section: Micro-raman Spectrum Of the Grown Particles At Various Condimentioning
confidence: 52%
“…The wave number of the Raman-active mode can be shifted toward lower values (down to 1310 cm −1 ) if the laser power used for exciting the Raman effect is increased. Zhao et al [32] have shown that such a shift can also be achieved by decreasing the grain size of diamond crystallites down to a few tens of nanometers. But it is not the case in our experiments.…”
Section: Discussionmentioning
confidence: 99%